Peningkatan Hasil Belajar Geografi Siswa Kelas XI IIS SMA 3 Enrekang dengan Menggunakan Metode Problem Based Learning - Amran, Amran (LaGeografia, 2019)
This study aims to find out: Is problem based learning learning can improve student learning outcomes in class XI IIS 3 in the eye This research is classroom action research (PTK) by conducting analytical techniques, there are those that will be analyzed are pretest (midterm scores) as the basic score then the final test results of the first cycle and second cycle and the activity data in the form of student activity sheets observed by the observer to find out the responses after the implementation of the problem based learming model. Learning outcomes before using the problem based leaning learning model 72.28% experienced an increase after being applied in the first cycle of 72.57% and the second cycle 78.85% with an increase of 8.33%. The results of observations of student activities in teaching and learning activities experienced changes in the first cycle 37.65% experienced changes in student learning activities in the second cycle 73.1% with the active category, this experienced improved attitude from the previous cycle.